Arte esquematico en la vertiente sur del Sistema Central - Alcolea Gonzalez, Jose Javier; Bunes Ibarra, Fernando de; Garcia Valero, Miguel Angel; Jimenez Sanz, Pedro José (Trabalhos de Antropologia e Etnologia, 2020)
.